PENGARUH CONGRUENCE DAN AROUSAL TERHADAP NIAT PEMBELIAN IMPULSIF DARING DI TIKTOK SHOP: MODERASI WISHFUL IDENTIFICATION - Silvana Rizkiyah; Osly Usman; Nofriska Krissanya (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of consumer-influencer congruence, consumer-product congruence, influencer-product congruence, and arousal on online impulse buying intentions among TikTok Shop users, with wishful identification as a moderating variable. The study used a quantitative approach by collecting data through questionnaires from respondents who had accessed and shopped at TikTok Shop, then analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method assisted by SmartPLS. The research model tested 8 hypotheses to explain the direct relationship and moderating effects between variables. The test results showed that of the 8 hypotheses proposed, 4 hypotheses were accepted and 4 hypotheses were rejected. The research findings indicate that not all congruence dimensions are consistently able to drive online impulse buying intentions, but the arousal variable is proven to have an important role in shaping spontaneous buying impulses in the context of social commerce on TikTok Shop. On the other hand, wishful identification shows a selective moderating role, so the effectiveness of the relationship between consumer, influencer, and product congruence on impulse buying intentions depends on the form of consumer psychological attachment to the influencer. This research provides theoretical contributions to the development of digital marketing and consumer behavior literature, as well as practical implications for business actors and marketers in designing more effective influencer-based promotional strategies to encourage impulse purchases on the TikTok Shop platform.